Physiological responses of two pedunculate oak (Quercus robur L.) families to combined stress conditions - drought and herbivore attack : Fiziološki odgovor dvije familije hrasta lužnjaka (Quercus robur L.) na kombinaciju stresa - suša i defolijatori - Pilipović, Andrej (Array, 2020)
Pedunculate oak (Quercus robur L.) is economically and ecologically one of the most important tree species in lowland forests of Southeastern Europe, and it is endangered by numerous biotic and abiotic factors. In this study, we investigated the effect of drought and herbivore attack of gypsy moth (Lymantria dispar L.) on two families of young oak seedlings subjected to the following treatments: drought (D); gypsy moth (GM); both drought and gypsy moth (D+GM) and control (Ø) for a period of 15 days followed by a 7-day recovery period. During both treatment and recovery, physiological parameters - net photosynthesis (A), transpiration (E), stomatal conductance (gs), sub-stomatal CO2 concentration (Ci), water use efficiency (WUE), nitrate reductase activity (NRA) and chlorophyll content (Chl) were measured. Our results showed significant effects of stress factors on physiological processes in oak seedlings which could have potential impact on forest regeneration. Also, differences in the reaction between investigated families indicated the need for breeding and selection of more resistant progenies and provenances of pedunculate oak.